Peran Tata Letak Tempat Duduk Siswa Dalam Mengelola Suasana Kelas di Lingkungan Sekolah Dasar Bunda Wacana - Vera Septiana; Sukma Wijayanto (Prosiding University Research Colloquium, 2021)
The study aims to find out how seating affects the atmosphere of grade school. It's aqualitative study. This research source is the fourth grade teacher of the mother of thewacana mageagle. Data collection techniques are observation and interview. Haisl'sresearch was that class management was performed by the teacher first to configureseating positions, classroom decorations, and class hygiene. The teacher performsoversight on the performance of each student's duties. After that it covered the students'learning efficiency after the sit-sit was changed and the previous.